Thinking and Deciding - Baron, Jonathan (UK Cambridge University Press, 2024)
The fifth edition of the classic text Thinking and Deciding updates the broad overview of the field of judgments and decisions offered in previous editions. It covers the normative standards used to evaluate conclusions, such as logic, probability, and various forms of utility theory. It explains descriptive accounts of departures from these standards, largely in terms of principles of cognitive psychology, emphasizing the distinction between search processes and inferences. Chapters cover decisions under risk, decision analysis, moral decisions and social dilemmas, and decisions about the future. Although the book assumes no particular prerequisites beyond introductory high-school algebra, it is most suited to advanced undergraduates, early graduate students, and active researchers in related fields, such as business, politics, law, medicine, economics, and philosophy.
Keywords: Phychology; Economics; Law